Immune interaction between SARS-CoV-2 and Mycobacterium tuberculosis - Booysen, Petro; Wilkinson, Katalin A.; Sheerin, Dylan; Waters, Robyn; Coussens, Anna K.; Wilkinson, Robert J. (Frontiers in Immunology, 2023)
SARS-CoV-2 and Mycobacterium tuberculosis (Mtb) are major infectious causes of death, with meta-analyses and population-based studies finding increased mortality in coinfected patients simultaneously diagnosed with COVID-19 and tuberculosis. There is a need to understand the immune interaction between SARS-CoV-2 and Mtb which impacts poor outcomes for those co-infected. We performed a PubMed and preprint search using keywords [SARS-CoV-2] AND [tuberculosis] AND [Immune response], including publications after January 2020, excluding reviews or opinions. Abstracts were evaluated by authors for inclusion of data specifically investigating the innate and/or acquired immune responses to SARS-CoV-2 and Mtb in humans and animal models, immunopathological responses in co-infection and both trials and investigations of potential protection against SARS-CoV-2 by Bacille Calmette Guérin (BCG). Of the 248 articles identified, 39 were included. Incidence of co-infection is discussed, considering in areas with a high burden of tuberculosis, where reported coinfection is likely underestimated. We evaluated evidence of the clinical association between COVID-19 and tuberculosis, discuss differences and similarities in immune responses in humans and in murine studies, and the implications of co-infection. SARS-CoV-2 and tuberculosis have both been shown to modulate immune responses, particularly of monocytes, macrophages, neutrophils, and T cells. Coinfection may result in impaired immunity to SARS-CoV-2, with an exacerbated inflammatory response, while T cell responses to Mtb may be modulated by SARS-CoV-2. Furthermore, there has been no proven potential clinical benefit of BCG despite numerous large-scale clinical trials.